Photoexcitation in thin films deposited on silicon substrates by reactive pulsed laser ablation. (2001) - Guidoni, A. Giardini; Marotta, V.; Orlando, S.; Parisi, G. P.
Abstract : Reactive pulsed laser ablation is a very interesting method to deposit thin films of several materials and compounds such as oxides, nitrides, semiconductors and superconductors. This technique relies on photoablation of pure elements, or a mixture of materials, with simultaneous exposure to a reactive atmosphere. In the case of oxides, reactions between the laser vaporized metals and oxygen lead to the formation of intermediate complexes and finally to oxide thin films. The reactivity of the plume has been already studied by our group in other oxides and nitrides productions and ascertained by Time of Flight Mass Spectrometry measurements [1]. Thin films of semiconducting oxides such asIn 2 O 3, SnO 2, and multilayers of these two compounds have been deposited by Reactive Pulsed Laser Ablation, with the aim to evaluate the behaviour of such films under variable halogen lamp illumination. Deposition of these thin films has been carried out by a frequency doubled Nd-YAG laser (wavelength = 532 nm) on Silicon (100) substrates. A comparison, among indium oxide, tin oxide, and multilayers of indium and tin oxides, has been performed. The influence of physical parameters, such as substrate temperature and oxygen pressure in the deposition chamber, has been investigated. The deposited films have been characterized by Electric Resistance measurements.